Columnar metaplasia in a surgical mouse model of gastro‐esophageal reflux disease is not derived from bone marrow‐derived cell - Aikou, Susumu (Cancer Sci, 2013)
The incidence of esophageal adenocarcinoma has increased in the last 25 years. Columnar metaplasia in Barrett's mucosa is assumed to be a precancerous lesion for esophageal adenocarcinoma. However, the induction process of Barrett's mucosa is still unknown. To analyze the induction of esophageal columnar metaplasia, we established a mouse gastro‐esophageal reflux disease (GERD) model with associated development of columnar metaplasia in the esophagus. C57BL/6 mice received side‐to‐side anastomosis of the esophagogastric junction with the jejunum, and mice were killed 10, 20, and 40 weeks after operation. To analyze the contribution of bone marrow‐derived cells to columnar metaplasia in this surgical GERD model, some mice were transplanted with GFP‐marked bone marrow after the operation. Seventy‐three percent of the mice (16/22) showed thickened mucosa in esophagus and 41% of mice (9/22) developed columnar metaplasia 40 weeks after the operation with a mortality rate of 4%. Bone marrow‐derived cells were not detected in columnar metaplastic epithelia. However, scattered epithelial cells in the thickened squamous epithelia in regions of esophagitis did show bone marrow derivation. The results demonstrate that reflux induced by esophago‐jejunostomy in mice leads to the development of columnar metaplasia in the esophagus. However, bone marrow‐derived cells do not contribute directly to columnar metaplasia in this mouse model.